It looked like spilt milk - Shaw, Charles Green, 1892- (New York : Harper & Row, 1988)
Illustrations show that a cloud may look like spilt milk, an ice cream cone, a tree, a mitten, a rabbit, or many other objects.
"Harper trophy book.".
2.0.
K-3
Keywords: Clouds -- Fiction; Imagination -- Fiction; Shape -- Fiction; Clouds -- Fiction; Imagination -- Fiction; Size and shape -- Fiction